Factors that influence the change of behavior of Young Prisoners in Prison: From the perception of Civil Servant JUSA C: Faktor-faktor yang mempengaruhi perubahan tingkah laku Banduan Muda di Penjara: Dari persepsi Penjawat Awam JUSA C - Abdul Raof, Azura; Hasan, Haslinda; Anuar, Azhan (Jurnal Pendidikan Bitara UPSI, 2023)
Every adolescent categorized as a young offender, young person on remand, young prisoner or juvenile offender is placed at Integrity School. They were found guilty of various criminal cases, from murder, rape, robbery, and others, subject to the Penal Code and the Children's Act. The study of 50 civil servants consisted of Grade C Principal Officers (JUSA C) following the Advanced Leadership and Management Program (ALMP). They held sessions with 112 young prisoners and young remand in Kajang Prison. This study applies   quantitative approach in the process of data collection and data analysis. This study aims  for the continuous evaluation of (JUSA C) civil servants to be able to make important decisions in several areas regarding the progress and implementation of the rehabilitation program and then facilitate  the next steps necessary by the Malaysian Prisons Department. Rehabilitation programs conducted in prisons successfully produce positive-minded juveniles through an adequate rehabilitation system, emphasis on disciplinary aspects, effective motivational programs, family support, and religious approaches to assist in rehabilitation before release. The study found that religious elements, family support and motivational programs are the main factors that successfully